Unmet needs in countries participating in the undiagnosed diseases network international: an international survey considering national health care and economic indicators - Sciascia, Savino; Roccatello, Dario; Salvatore, Marco; Carta, Claudio; Cellai, Laura L.; Ferrari, Gianluca; Lumaka, Aimè; Groft, Stephen; Alanay, Yasemin; Azam, Maleeha; Baynam, Gareth; Cederroth, Helene; et al. (Frontiers in Public Health, 2023)
Background: Patients, families, the healthcare system, and society as a whole are all significantly impacted by rare diseases (RDs). According to various classifications, there are currently up to 9,000 different rare diseases that have been recognized, and new diseases are discovered every month. Although very few people are affected by each uncommon disease individually, millions of people are thought to be impacted globally when all these conditions are considered. Therefore, RDs represent an important public health concern. Although crucial for clinical care, early and correct diagnosis is still difficult to achieve in many nations, especially those with low and middle incomes. Consequently, a sizeable amount of the overall burden of RD is attributable to undiagnosed RD (URD). Existing barriers and policy aspects impacting the care of patients with RD and URD remain to be investigated. Methods: To identify unmet needs and opportunities for patients with URD, the Developing Nations Working Group of the Undiagnosed Diseases Network International (DNWG-UDNI) conducted a survey among its members, who were from 20 different nations. The survey used a mix of multiple choice and dedicated open questions covered a variety of topics. To explore reported needs and analyze them in relation to national healthcare economical aspects, publicly available data on a) World Bank ranking; b) Current health expenditure per capita; c) GDP per capita; d) Domestic general government health expenditure (% of GDP); e) Life expectancy at birth, total (years) were incorporated in our study. Results: This study provides an in-depth evaluation of the unmet needs for 20 countries: low-income (3), middle-income (10) and high-income (7). When analyzing reported unmet needs, almost all countries (N = 19) indicated that major barriers still exist when attempting to improve the care of patients with UR and/or URD; most countries report unmet needs related to the availability of specialized care and dedicated facilities. ABSTRACT HAS BEEN IMPLEMENTED BEYOND THE LIMIT TO ADDRESS REVIEWERS' QUERY